WeChat use of mainland Chinese dual migrants in daily border crossing. Issue 4 (2nd October 2019) - Ju, Bei; Sandel, Todd L.; Thinyane, Hannah
Abstract : Drawing on data derived from WeChat and the life experiences of its users, this study explores the daily affordances of WeChat in the cross-border lives of dual migrants from the Chinese mainland. In this study, 24 low-skilled Chinese dual migrants from the mainland who were working as security guards and cleaners were recruited to participate in in-depth interviews and group discussions. The lives of these dual migrants are marked politically, socially, and economically by their vulnerable status and by the stresses and vicissitudes that characterize their daily commute between Zhuhai (their place of residence) and Macao (their place of work). Dual migrants from the Chinese mainland use electronic media for support, pleasure, and access to information. One of the main online platforms they utilize is WeChat, a social networking site that is available on mobile phones. By framing these dual migrants' usage of WeChat within the affordances of social media, this social networking site functions as a digital mediated space that provides migrants with communal solidarity, social interaction, access to information, and, in some cases, economic benefits.